Microbial Antibiotic Resistance: - K. A. Vinogradova; V. G. Bulgakova; A. N. Polin; P. A. Kozhevin (Антибиотики и Химиотерапия, 2020)
The known conceptions of resistome as a complex of all the antibiotic resistance genes in the genomes of all the microorganisms, pathogenic and nonpathogenic ones, in nature are considered. The data on the origin, evolution and distribution of antibiotic resistance genes and possible approaches to the resistance distribution control are presented.